Analisis Pengaruh Perputaran Piutang Terhadap Likuiditas Perusahaan Studi Kasus Pada PT. GOODYEAR Indonesia Tbk. dan PT. Gajah Tunggal Tbk. - Surya, Tarida Marlin; Nugraha, Achmad Fajar (Jurnal Ilmiah Ranggagading (JIR), 2012)
The purpose of this study was to determine the effect of receivables turnover on the companys liquidity. Level of liquidity is measured using the current ratio, quick ratio and cash ratio. Data collection techniques used were secondary data obtained in the corner of the Indonesia Stock Exchange in the form of financial statements of companies engaged in the automotive sector from 2005-2009. The method used is descriptive method that aims to explain in a systematic and accurate way the facts and characteristics of the population or certain things that will be studied.The study uses analysis of turnover (ARTO) and liquidity ratios, while the object of research is PT. Goodyear Indonesia Tbk. and PT. Gajah Tunggal Tbk. From these results, PT. Goodyear Indonesia Tbk. during 2005 to 2009 always changed the level of turnover and liquidity level. The highest turnover rate was in 2009 that equals to 12.28 times, while the lowest turnover rate was in 2005 that equals to 7.93 times. The highest level of liquidity ini 2006 of 222.69% while the lowest level of liquidity in the year 2009 amounted to 90.48%. PT. Gajah Tunggal Tbk. changed every year. Receivables turnover rate was highest in 2009 amounting to 11.33 time while the lowest turnover rate in 2005 was 7:56 times. The highest level of liquidity was in the year 2009 amounting to 253.18% while the lowest level of liquidity in 2008 was 147%.